Evaluation of resistance to displacement of metal posts with different lengths - Ana Paula Farina; Doglas Cecchin; Aloísio Oro Spazzin; Fernanda de Carvalho Panzeri Pires-; Nereu Roque Dartora; Marcelo Ferraz Mesquita (Wolters Kluwer Medknow Publications, 2012)
Aims and Objectives: to evaluate the resistance to displacement of metal intraradicular retainers of different lengths by means of the shear test. Material and Methods: Thirty-six maxillary central incisors were cross-sectioned at 16 mm from the root apex, endodontically treated and randomly divided into three groups that were treated as follows: G1 (control) preparation of 2/3 (10.6 mm) of the total root length; G2: preparation of 1/2 (8 mm) of the total root length and G3: preparation of 1/3 (5.3 mm) of the total root length. After canal preparation, a matrix was made of the coronal and radicular portions using Duralay to obtain metal intraradicular retainers. These retainers were cemented with zinc phosphate cement and subjected to the compression shear test in a Universal Test Machine (EMIC DL 2000) at a crosshead speed of 0.5 mm/minute. The results were subjected to statistical analysis by analysis of variance (ANOVA) and Newman- Keuls, which showed statistically significant difference (P < 0.01). Results: The means in Newtons and their respective standard deviations were: G1 = 972.05 (±81.36); G2 = 921.15 (±112.25); G3 = 686.66 (±113.02). Conclusion: It could be concluded that metal retainers of 2/3 and 1/2 the length of the root portion showed higher resistance to displacement values when compared with the group that had been prepared for 1/3 of the root length.